A new species of the genus Theloderma Tschudi, 1838 (Anura: Rhacophoridae) from Northwestern Vietnam - Bain, Raoul H.; Nguyen, Truong Q.; Doan, Kien V. (Zootaxa, 2009)
A new species of Theloderma is described from the Hoang Lien Mountains of northwestern Vietnam from between 1300–1400 m elevation. Theloderma lateriticum sp. nov. was found at night inside a water-filled chamber of bamboo, which was within disturbed, submontane, semi-evergreen forest. The new species of Theloderma can be immediately differentiated from all other congeners by its solid, brick-red dorsal wash and minimal foot webbing (proximal to proximal subarticular tubercle on Toe I; to level of proximal subarticular tubercle on postaxial side of II; proximal to proximal subarticular tubercle on preaxial side of III; just beyond proximal subarticular tubercle on postaxial side of III; to level of proximal subarticular tubercle on preaxial side of IV; just beyond proximal subarticular tubercle on postaxial side of IV; and just beyond proximal subarticular tubercle on preaxial side of V). The female and tadpole remain unknown.